Status of Wetland Birds in Kanyakumari, Thanjavur, Cuddalore and Nagapattinam Districts of Tamil Nadu, India - Sridharan, N.; Somasundaram, S.; Thiyakesan, K.; Vijayan, Lalitha (Indian Forester, 2011)
Wetlands are important bird habitats and are also used by local people for their livelihoods. Study was undertaken to assess the status of the wetland birds in the selected wetlands by using total count method during January-March 2006. Forty two major wetlands were surveyed in four districts of Tamilnadu namely Kanyakumari, Thanjavur, Cuddalore and Nagapattinam. Totally 15,616 individual birds belonging to 65 species of 31 families were recorded. Out of the 65 species recorded, 42 were wetland and 23 were terrestrial species. The most common bird family in the study area was Ardeidae (Commonness index=0.33) followed by Anatidae (Commonness index=0.27). One threatened and two near threatened species namely, spot-billed pelican (Pelicanus philippensis) (VU), painted stork (Mycteria leucocephala) (NT) and darter (Anhinga melanogaster) (NT) were recorded.